Obesity and the diagnostic accuracy for primary aldosteronism. Issue 8 (13th June 2017) - Tirosh, Amit; Hannah‐Shmouni, Fady; Lyssikatos, Charalampos; Belyavskaya, Elena; Zilbermint, Mihail; Abraham, Smita B.; Lodish, Maya B.; Stratakis, Constantine A.
Abstract : The effects of body mass index on the diagnostic accuracy of primary aldosteronism (PA) are inconsistent and yet important considering the high prevalence and frequent co‐occurrence of obesity and hypertension. The current study included 59 adult patients who underwent a stepwise evaluation for PA, using aldosterone to renin ratio for case detection and plasma aldosterone concentration after saline suppression test and/or 24‐hour urinary aldosterone after oral sodium loading for case confirmation. Body mass index had a quadratic (U‐shaped) correlation with plasma aldosterone concentration, plasma renin activity, aldosterone to renin ratio, and plasma aldosterone concentration after saline suppression test. Among patients with a body mass index ≥30 kg/m 2, the aldosterone to renin ratio yielded lower case detection accuracy of PA. We conclude that obesity results in a nonlinear correlation with plasma aldosterone concentration, plasma renin activity, and aldosterone to renin ratio, which affects the accuracy of case detection for PA. Patients with a body mass index ≥30 kg/m 2 are less accurately identified as having PA when saline suppression and/or oral salt loading tests are used for case confirmation.